Hydrogenation of methyl levulinate to γ‐valerolactone over Cu─Mg oxide using MeOH as in situ hydrogen source. Issue 1 (27th July 2018) - Cao, Xuejuan; Wei, Junnan; Liu, Huai; Lv, Xinyue; Tang, Xing; Zeng, Xianhai; Sun, Yong; Lei, Tingzhou; Liu, Shijie; Lin, Lu
Abstract: BACKGROUND: γ‐Valerolactone (GVL) is a versatile biomass‐derived platform molecule that could serve as a building block to produce chemicals, materials and fuels, but the production of GVL from biomass via a cost‐competitive method is challenging. In this contribution, a robust Cu─Mg oxide was prepared as an efficient bifunctional catalyst for both H2 production by MeOH reforming and hydrogenation of methyl levulinate (ML) to GVL in MeOH medium. RESULTS: Cu0.87 Mg0.13 Ox prepared by a urea hydrolysis method offered a GVL yield up to 90.6% at 220°C in 4 h without external hydrogen. This catalyst could be reused for at least seven consecutive cycles without loss of its activity. Notably, Cu0.87 Mg0.13 Ox also provided nearly 70% GVL yield in methanolysis products of cellulose in the presence of humins. Characterization of the catalyst indicates that the incorporation of MgO greatly facilitates the stabilization of Cu + species that possess a better catalytic performance in ML hydrogenation compared with metallic Cu. CONCLUSION: This robust Cu0.87 Mg0.13 Ox could greatly contribute to develop a highly facile and desirable two‐step strategy for GVL production from cellulose, through the integration of ML production by methanolysis of cellulose, H2 formation by MeOH reforming and ML hydrogenation in MeOH medium. © 2018 Society of Chemical Industry